The Fleming Method for Tissue and Vascular Differentiation and Metabolism-Finding breast cancer in women with breast implants - Richard M Fleming; Matthew R Fleming; Tapan K Chaudhuri; William C Dooley (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Women with both dense breasts and breast implants present a special challenge for consideration due to the increased incidence of false-positives and false-negatives with mammography [1]. Molecular Breast Imaging [MBI] has provided limited proven benefit until recently, when improvements in camera calibration, enhancement and quantification [2,3], resulted in the ability to differentiate tissue based upon measurable changes in regional blood flow and metabolism [4].